The impact of industrial training on career challenges and motivations among Malaysian public universities students - Anak Jery, Tiffany Audrey; Ma’rof, Aini Azeqa; Rosnon, Mohd Roslan (Human Resource Management Academic Research Society, 2024)
This study explores the relationship between industrial training experiences, challenges, and career motivations among final-year students in Malaysian public universities. The research examines how key dimensions of industrial training—knowledge, practices, and skills— impact students' ability to navigate workplace challenges and foster career motivations, including career insight, identity, and resilience. A sample of 400 students was analyzed using quantitative methods, including correlation and regression analyses. The results indicate that industrial training significantly influences both the challenges students face and their career motivations, with knowledge being the strongest predictor. Practices and skills also contributed positively to career motivation, while structured mentorship and feedback during training played a crucial role in overcoming workplace challenges. These findings emphasize the importance of well-structured industrial training programs in preparing students for the workforce and developing their professional resilience and career commitment. This study provides valuable insights into how industrial training shapes students' career trajectories and offers practical implications for improving the design of industrial training programs in higher education.